Donor selection in heart transplantation - Kilic, Ahmet (Pioneer Bioscience Publishing Company, 2014)
There is increased scrutiny on the quality in health care with particular emphasis on institutional heart transplant survival outcomes. An important aspect of successful transplantation is appropriate donor selection. We review the current guidelines as well as areas of controversy in the selection of appropriate hearts as donor organs to ensure optimal outcomes. This decision is paramount to the success of a transplant program as well as recipient survival and graft function post-transplant.